Core descriptors for in situ conservation of crop wild relatives v.1. - Thormann, I.; Alercia, A.; Dulloo, Mohammad Ehsan (Bioversity International, 2013)
Crop wild relatives (CWR) are wild plant species that are more or less closely related to domesticated species, include crop progenitors and are a potential source of traits beneficial to our crops. Given their importance for agricultural research and development, their conservation is of high priority, in particular their in situ conservation that allows continued evolution of new adaptive traits as well as the maintenance of the breadth of genetic diversity present in the many CWR species. The core descriptors for in situ conservation of CWR are designed to facilitate the compilation and exchange of data, which are needed to develop and implement in situ conservation activities. They are compatible with Bioversity’s crop descriptor lists, the ‘FAO/Bioversity List of Multi-Crop Passport Descriptors V.2’ and IUCN red listing categories and criteria.